Stability and bioaccessibility of anthocyanins from maqui (Aristotelia chilensis [Mol.] Stuntz) juice microparticles. (May 2018) - Fredes, Carolina; Osorio, María Jesús; Parada, Javier; Robert, Paz
Abstract: The microencapsulation of maqui juice by spray-drying was studied as a strategy to protect anthocyanins in new value-added formulations. The objective of this research was to study the influence of each maqui-anthocyanin and encapsulating agent (inulin or sodium alginate) on the anthocyanin encapsulation efficiency, the stability during storage (160 days at 60 °C) and the bioaccessibility in in vitro digestion model. The highest encapsulation efficiency of anthocyanins (65.6–78.6%) was obtained with inulin. The chemical structure of anthocyanins also influenced the encapsulation efficiency; the highest was 78.6% for delphinidin-3-sambubioside-5-glucoside in maqui juice-inulin, and 51.2% for cyanidin-3-glucoside in maqui juice-alginate. For both maqui juice-inulin and maqui juice-alginate microparticles, the half-life values of delphinidin-3-sambubioside (198 days), delphinidin-3-glucoside (173–182 days) and cyanidin-3-glucoside (154-133 days) showed the lowest stability of 3- O -glycosylated anthocyanins. The bioaccessibility of anthocyanins of the maqui juice microparticles was 10% higher than maqui juice. Highlights: 3, 5- O -diglycosylated anthocyanins had the highest stability at accelerated storage conditions. The stability of anthocyanins showed different behaviors in in vitro digestion model. The microencapsulation of maqui juice increase in a 10% the bioaccesibility of anthocyanins.